PENGARUH EDUKASI MANFAAT ASI COLOSTRUM MELALUI MEDIA POSTER TERHADAP PENGETAHUAN IBU POST PARTUM - Nelfa F Takahepis; Dewi A Sudijanto; Petronela Mamentu (Jurnal Riset Multidisiplin Edukasi, 2026)
Breastfeeding is a natural process, but many new mothers find it one of the most amazing parts of motherhood. Through health education, mothers can understand the benefits of colostrum, such as strengthening the baby's immune system, improving digestion, and preventing infections. The purpose of this study was to determine the effect of Lactation Education through Leaflet Media on Colostrum Breastfeeding in Post Partum at Bhayangkara Gr. III Hospital Manado. This research is experimental with pre experimental research design and using the "One group pretest-posttest method. The population in this study were post partum mothers in Bhayangkara Hospital Manado as many as 48 people, the sampling technique used random sampling technique which was a random sample using the Slovin formula, so there were 7 samples. The results of this study are based on statistical tests Paired T test results showed a value of p = 0.000 with a p value = 0.035 which both of these values are less than the value of a = <0.05. From these results, it can be interpreted that in this study Ha is accepted and H0 is rejected in other words there is an effect of Lactation Education through Leaflet Media on Knowledge and Attitudes of Colostrum Breastfeeding in Post Partum at Bhayangkara Gr. III Hospital Manado. The conclusion of this study was that mothers who received education through leaflets tended to have better knowledge and a more positive attitude towards colostrum feeding than those who were not given education. This happens because leaflets can be read repeatedly, making it easier for mothers to remember and understand the contents of the message conveyed.